Property and carceral spaces in Christiania, Copenhagen - Rannila Päivi; Repo Virve (SAGE, 2022)
This article addresses the recent legal and property changes, and their socio-spatial
consequences in Christiania, Copenhagen. During recent years the community that has always
been against private ownership has lost its special legal status, and became a property owner
of a vast area in the middle of Copenhagen. We analyze the situation in relation to Christiania’s
current housing condition, individual residents’ privatization efforts, and decades-long
normalization efforts by the state. We argue that the processes of normalization, legalization,
criminalization and privatization are expressions of the carceral in more-than-institutional
context, and that questions of property are strongly involved in these carceral practices in
Christiania. Not only in the relations between Christiania and the state, but also in socio-spatial
relations inside of the community, defining who is included or excluded, or how people behave
towards each other. Moreover, a part of the community is cultivating a carceral culture
towards those in favor of privatization, using the rights of the property owner and the
community’s ideologies as justifications.